Comparison of transvenous vs subcutaneous defibrillator therapy in patients with cardiac arrhythmia syndromes and genetic cardiomyopathies - Kuschyk, Jürgen; Müller-Leisse, Johanna; Duncker, David; Tueluemen, Erol; Fastenrath, Fabian; Fastner, Christian; Kruska, Mathieu; Akın, Ibrahim; Liebe, Volker; Borggrefe, Martin; Veltmann, Christian; Rudic, Boris (International journal of cardiology, 2021)
Background - Inherited arrhythmia syndromes and genetic cardiomyopathies attribute in a significant proportion to sudden cardiac death. Implantable cardioverter defibrillators (ICDs) are the cornerstone in the prevention of sudden death in high-risk patients. However, ICD therapy is also associated with high rates of inappropriate shocks and/or device-related complications especially in young patients. - Objective - To determine the outcome of high-risk patients with inherited arrhythmia syndromes and genetic cardiomyopathies comparing two defibrillator technologies. - Method - Between 2010 and 2018, 183 consecutive patients from two large German tertiary care centers were enrolled in the study. The majority of patients (83%) had either cardiac channelopathies or idiopathic ventricular fibrillation without cardiac structural abnormalities, while the remaining 17% had a genetic cardiomyopathy (HCM/ARVC). Eighty-six patients (47%) received a transvenous ICD (TV-ICD), while a subcutaneous ICD (S-ICD) was implanted in another 97 patients (53%). - Results - During a mean follow-up of 4.3 years, 30 patients had an appropriate ICD therapy (annual rate 3.8%). Fifteen patients experienced an inappropriate shock (annual rate 1.9%). Lead failure occurred in 17 (9%) patients and was less frequent in the S-ICD group (OR 0.48, 95%CI 0.38-0.62). Adverse defibrillator events, defined as a composite of inappropriate shocks and lead failure requiring surgical revision were significantly lower in the S-ICD group as compared to the TV-ICD group (OR 0.55, 95%CI 0.41-0.72). There was a non-significant trend towards lower appropriate shocks in the S-ICD group, that in combination with all-cause shocks yielded in a significantly higher freedom of any shock in the S-ICD group (RR 39%, p = 0.003). No deaths occurred during follow-up. - Conclusion - The present data favor the use of the subcutaneous ICD for patients with inherited arrhythmia syndromes and genetic cardiomyopathies who do not need anti-bradycardia pacing.